The Effect of Service Quality and Facilities on the Satisfaction of BPJS Class 1 Patients with Hospital Image as an Intervening Variable at the Non-class Inpatient Installation of Tangerang General Hospital - Maryani, Rani; Widjaja, Bernard T.; Purnama, Eka Desy (Global Writing Academica Researching & Publishing, 2024)
The non-class service implemented in the inpatient installation of Tangerang General Hospital causes all BPJS insurance participants to receive class 3 services and facilities. This raises the question of whether BPJS class 1 participants are satisfied with the services they receive and what innovations need to be implemented by Tangerang General Hospital. This study uses a quantitative method that aims to determine the effect of service quality and facilities on hospital image so that it affects the satisfaction of class 1 patients in the non-class inpatient installation of Tangerang General Hospital. The research sample taken was class 1 BPJS patients who were admitted to the inpatient installation of Tangerang General Hospital in August - September 2023, with a total sample of 85 respondents. Data were obtained through questionnaires distributed according to the inclusion and exclusion criteria. The analysis technique used was SEM-PLS (Structural Equation Model-Partial Least Square). The results show that all hypotheses are supported by existing data, where it is proven that the quality of service and facilities each has a significant positive effect on patient satisfaction. The results also show that hospital image mediates the positive effect of service quality on patient satisfaction and mediates the positive effect of facilities on patient satisfaction